THE POSSIBILITIES OF DEVELOPING COMPUTATIONAL THINKING IN PRIMARY EDUCATION - BRYNDOVÁ, Lucie (Trends in education, 2021)
This paper summarizes the current academic discussion on the implementation of the computational thinking development at the level of state curricula, both in the Czech Republic and foreign states. It summarizes partial contents of selected curricula and their understanding of computational thinking and compares the reform taking place in the Czech Republic with foreign experiences. The article consists of four chapters, which deal with the concept of computational thinking in the upcoming reform of the FEP, the issue of developing computational thinking in compulsory education aboard, partial contents of curricula with regard to the understanding of the concept of CT and the possibility of the implementation the development of CT into the national curriculum. The article partly addresses issues faced by the implementation of the curricular revision abroad.
Keywords: Computational Thinking; Primary School Pupils; Informatics At Primary School; Computer Science Curriculum Revision